2020
DOI: 10.21203/rs.2.22383/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of medical student competency, attitudes and knowledge of abortion care after a structured clinical curriculum

Abstract: Background: Abortion care is a core educational objective according to the Association of Professors of Gynecology and Obstetrics (APGO), but clinical exposure is variable in medical education. The authors sought to compare professional competency, attitudes, and knowledge regarding abortion between students who attended a structured clinical experience in abortion care to those who chose a less-structured family planning clinical environment.Methods: All medical students participating in the Obstetrics & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
Order By: Relevance
“…3,8,18,27,30,32,33,38,48 Twenty-one USA studies assessed clinical students during their third year clerkships. 2,4,5,9,[11][12][13][14][15][16][17]19,[21][22][23]26,28,31,40,49,55 Two studies assessed sexual and reproductive health education from all years in medical school through surveys of faculty with knowledge of the curriculum. 7,53 Six studies assessed fifth and/or sixth year students about sexual and reproductive health education.…”
Section: Training Level Of Students Assessedmentioning
confidence: 99%
See 4 more Smart Citations
“…3,8,18,27,30,32,33,38,48 Twenty-one USA studies assessed clinical students during their third year clerkships. 2,4,5,9,[11][12][13][14][15][16][17]19,[21][22][23]26,28,31,40,49,55 Two studies assessed sexual and reproductive health education from all years in medical school through surveys of faculty with knowledge of the curriculum. 7,53 Six studies assessed fifth and/or sixth year students about sexual and reproductive health education.…”
Section: Training Level Of Students Assessedmentioning
confidence: 99%
“…The authors found improved student knowledge after the education but that knowledge decreased after a year. 4,5 Additional studies described improvements in students' selfassessment of knowledge, 2,20 comfort, 8,13 confidence, 18,20,52 and competency 9 after an educational intervention on sexual and reproductive health topics.…”
Section: Student Knowledge Assessmentmentioning
confidence: 99%
See 3 more Smart Citations